Exploring the effect of corpus-informed and conventional homework materials on fostering EFL students' grammatical construction learning. (February 2022) - Rodríguez-Fuentes, Rodrigo A.; Swatek, Aleksandra M.
Abstract: Much research has been conducted on whether and to what extent corpus-based materials support more effective EFL learning in comparison to traditional materials. Little is known, however, about the effectiveness of different types of homework materials on students' grammatical performance. This classroom-based study addressed this gap by examining what effect two types of published materials—corpus-informed (CI) and non-corpus informed (NCI) grammar textbooks—have on the learning of one grammatical construction (post-predicate –ing and infinitive clauses controlled by verbs) in a group of 89 EFL learners in Colombia. The learners were randomly assigned to two treatments: CI and NCI material for homework. The results from pretest, post-test, and delayed test showed that both groups displayed significant gains in terms of their knowledge of the target construction. The effect was larger for the CI group than the NCI group, providing evidence for the potential advantage of CI material use for homework as a supplement for instruction. We suggest that CI textbooks be considered by teachers and learners who want to benefit from innovative commercial teaching materials (i.e., corpus-informed textbooks), especially in locations where innovative teaching practices (computer-based or data-driven learning) are restricted due to infrastructure limitations.